2017
DOI: 10.1007/s13361-017-1721-0
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism Behind Top-Down UVPD Experiments: Making Sense of Apparent Contradictions

Abstract: Top-down UVPD enables greater sequence coverage than any other currently available method, often fracturing the vast majority of peptide bonds in whole proteins. At the same time, UVPD can be used to dissociate noncovalent complexes assembled from multiple proteins without breaking any covalent bonds. Although the utility of these experiments is unquestioned, the mechanism underlying these seemingly contradictory results has been the subject of many discussions. Herein, some fundamental considerations of photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 36 publications
4
102
0
Order By: Relevance
“…It is also possible that fragment ions rearrange into a stable conformation on a timescale faster than we are able to measure. Further to this, some reports have indicated that lack of a specific UVPD fragment does not necessarily indicate strong non-covalent associations and suggests a combination of direct dissociation coupled with internal conversion (CID like) events [ 70 , 71 ] however in ECD experiments it is well-established that lack of fragments correlates with strong non-covalent associations [ 24 , 25 , 36 , 72 ]. For ubiquitin, as shown above, and as shall be shown for cytochrome c and myoglobin (below), we can interpret the UV-induced fragments in terms of regions of the proteins that are less encumbered by non-covalent associations.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that fragment ions rearrange into a stable conformation on a timescale faster than we are able to measure. Further to this, some reports have indicated that lack of a specific UVPD fragment does not necessarily indicate strong non-covalent associations and suggests a combination of direct dissociation coupled with internal conversion (CID like) events [ 70 , 71 ] however in ECD experiments it is well-established that lack of fragments correlates with strong non-covalent associations [ 24 , 25 , 36 , 72 ]. For ubiquitin, as shown above, and as shall be shown for cytochrome c and myoglobin (below), we can interpret the UV-induced fragments in terms of regions of the proteins that are less encumbered by non-covalent associations.…”
Section: Resultsmentioning
confidence: 99%
“…The low energy structures of [Leu-Enk + H] + are dominated by interactions of the -NH 3 + group with surrounding carbonyls. 10,19 This interaction can be significantly reduced by complexing the molecule with a 18-crown-6 molecule (CE), which has a high affinity towards protonated amines 27 and is expected to coordinate with the -NH 3 + group. Due to steric constraints, the CE solvated -NH 3 + group will not be able to interact strongly with other groups.…”
Section: Ir Spectroscopy Of [Leu-enk + Ce + H] + and [Leu-enk D + Ce mentioning
confidence: 99%
“…7 This possibility has prompted many studies of CEs with peptides and proteins. 8,9 The utilization of CEs in medical applications is emerging. 10,11 For example, amino-crown ethers have been utilized for the delivery of 5-fluorouracil (5-FU), an anticancer agent used for the treatment of metastatic carcinomas of pancreas and breast.…”
Section: Introductionmentioning
confidence: 99%